Building an International Entrepreneurial Faculty Ecosystem - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
At the Faculty of Business and Management, we realise that universities and industry have much to learn from one another. This collaboration ensures that our graduates meet and align with industrial standards. Therefore, partnerships between the two can be mutually beneficial while serving the university's entrepreneurial students.